Student perception of teaching quality in higher education - Pavlina, Krešimir; Pongrac Pavlina, Ana; Banek Zorica, Mihaela (2011)
This paper presents longitudinal research that examines how students perceive certain teaching quality characteristics which are measured by teaching assessment surveys conducted by the University of Zagreb. Main aim of this research is to find out how students rank teaching quality characteristics, their attitude towards teaching quality assessment surveys and their influence on improvement of teaching practice. Students are asked to rank by importance teaching quality characteristics by on-line survey. Similar research was conducted in years 2007 and 2009, so this paper will also present comparison of results between these three researches which displays refinement of student's perception of teaching quality characteristics. Findings from this research helps teachers to prioritize their effort to improve quality of teaching in those teaching quality characteristics that are identified by students as most important.
Projekt MZOS
ENG